Analysis of handgrip strength, pulling force using the upper limbs, and ground reaction forces in the task of boarding a bus between healthy elderly individuals and those with Parkinson's disease. - Miri, Andressa; Araújo, Hayslenne; Gil, André; de Oliveira, Marcio; Volpe, Renata; Angelo, Edylaine; Mahmoud Smaili, Suhaila (Physiotherapy Theory & Practice, 2024)
Elderly individuals with neurodegenerative diseases, such as Parkinson's disease (PD), may experience difficulties when performing functional tasks. To analyze the handgrip strength, pulling force, and ground reaction forces (GRF) of individuals with and without PD when boarding a bus while performing both simple (ST) and dual tasks (DT). This case-control study addressed 31 individuals with PD (GPD) and 30 healthy individuals (GHI). Assessments were performed in ST and DT situations using a bus model (prototype). Handgrip strength and pulling force were measured in both upper limbs using a dynamometer, and GRF was measured using a force platform. The GPD's and GHI's performances were compared in both ST and DT, and the individuals were classified as fallers according to the Falls Efficacy Scale. In the inter-group comparison, the GPD presented significantly lower maximum force using their right hand, in handgrip strength (30.43 vs. 36.62, P =.022), and pulling force (10.77 vs 12.81, P =.037). The left hand's pulling force proved to be the most demanding for the GPD, during ST (6.35 vs. 4.76, P =.006) and DT (6.32 vs 4.74, P =.008). The GPD also took longer to perform ST (6.14 vs. 4.67, P <.001) and DT (6.08 vs. 4.81, P =.002). Additionally, the GPD was more afraid of falling compared to the GHI (34.74 vs. 24.77, P <.001). Boarding a bus is a complex task for individuals with PD because they present lower maximum strength in the upper limbs and more significant functional expenditure than their healthy counterparts.